Structural Characteristics and Physical Properties of Tectonically Deformed Coals. (4th September 2012) - Ju, Yiwen; Yan, Zhifeng; Li, Xiaoshi; Hou, Quanlin; Zhang, Wenjing; Fang, Lizhi; Yu, Liye; Wei, Mingming
Abstract : Different mechanisms of deformation could make different influence on inner structure and physical properties of tectonically deformed coal (TDC) reservoirs. This paper discusses the relationship between macromolecular structure and physical properties of the Huaibei-Huainan coal mine areas in southern North China. The macromolecular structure and pore characteristics are systematically investigated by using techniques such as X-ray diffraction (XRD), high-resolution transmission electron microscopy (HRTEM), electron paramagnetic resonance (EPR), nuclear magnetic resonance (NMR), and low-temperature nitrogen adsorption method. The results suggest that under the directional stress, basic structural units (BSU) arrangement is closer, and the orientation becomes stronger from brittle deformed coal to ductile deformed coal. Structural deformation directly influences the macromolecular structure of coal, which results in changes of pore structure. The nanoscale pores of the cataclastic coal structure caused by the brittle deformation are mainly mesopores, and the proportion of mesopores volume in ductile deformed coal diminishes rapidly. So the exploration and development potential of coalbed gas are good in reservoirs such as schistose structure coal, mortar structure coal and cataclastic structure coal. It also holds promise for a certain degree of brittle deformation and wrinkle structure coal of low ductile deformation or later superimposed by brittle deformation.